Interventions for Alleviating Loneliness among Older Persons: A Critical Review. Issue 3 (January 2015) - Cohen-Mansfield, Jiska; Perach, Rotem
Objectives: Loneliness is common among older persons and has been associated with health and mental health risks. This systematic review examines the utility of loneliness interventions among older persons. Data Source: Thirty-four intervention studies were used. Study Inclusion Criteria: The study was conducted between 1996 and 2011, included a sample of older adults, implemented an intervention affecting loneliness or identified a situation that directly affected loneliness, included in its outcome measures the effects of the intervention or situation on loneliness levels or on loneliness-related measures (e.g., social interaction), and included in its analysis pretest-posttest comparisons. Data Extraction: Studies were accessed using the databases PsycINFO, MEDLINE, ScienceDirect, AgeLine, PsycBOOKS, and Google Scholar for the years 1996–2011. Data Synthesis: Interventions were classified based on population, format, and content and were evaluated for quality of design and efficacy. Results: Twelve studies were effective in reducing loneliness according to the review criteria, and 15 were evaluated as potentially effective. The findings suggest that it is possible to reduce loneliness by using educational interventions focused on social networks maintenance and enhancement. Conclusions: Multiple approaches show promise, although flawed design often prevents proper evaluation of efficacy. The value of specific therapy techniques in reducing loneliness is highlighted and warrants a wider investigation. Studies of special populations, such as the cognitively impaired, are also needed.